The Crimes of the Powerful: Between Force and Consensus - Vincenzo Ruggiero (Social Sciences, 2021)
Power entails the ability to act and overcome the obstacles erected by those who are subject to it. It also entails the capacity to make one’s crimes acceptable, while formulating criminal imputations against others. The crimes of the powerful, in this contribution, are examined through the lenses of a number of intertwined variables: coercion, legitimacy, violence, secrecy, consensus, and hegemony. Ostentation, imitation, and admiration are also considered as components of these types of crimes and the feelings they elicit. While the controversies surrounding legal responses to the crimes of the powerful are discussed, the efficacy of concerted action against them is optimistically invoked.